2018
DOI: 10.20944/preprints201807.0248.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Lubrication by Ionic Liquids: Activated Slip and Flow

Abstract: The present study provides molecular insight into the mechanisms underlying energy dissipation and lubrication of a smooth contact lubricated by an ionic liquid. We have performed normal and lateral force measurements with a surface forces apparatus and by colloidal probe atomic force microscopy on following model systems: 1-ethyl-3-methyl imidazolium bis-(trifluoro-methylsulfonyl)imide, in dry state and in equilibrium with ambient (humid) air; the surface was either bare mica or functionalized with a polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…13 A recent colloid probe study on [C 2 C 1 Im][NTf 2 ] reported an increase of friction for the liquid equilibrated with 44% RH compared to the dry liquid. 35 Molecular dynamics simulations also showed an increase in friction with added water. 42 In those cases, the films were often determined to be solid-like; i.e.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…13 A recent colloid probe study on [C 2 C 1 Im][NTf 2 ] reported an increase of friction for the liquid equilibrated with 44% RH compared to the dry liquid. 35 Molecular dynamics simulations also showed an increase in friction with added water. 42 In those cases, the films were often determined to be solid-like; i.e.…”
Section: Resultsmentioning
confidence: 96%
“…13 A recent colloid probe study on [C 2 C 1 Im][NTf 2 ] reported an increase of friction for the liquid equilibrated with 44% RH compared to the dry liquid. 35 Molecular dynamics simulations also showed an increase in friction with added water. 42 In those cases, the films were often determined to be solidlike; i.e., with some elastic characteristics; shearing the film is then an activated process, involving either translation of layers across one another or shear-melt.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…46,47 A similar collective motion of the IL ions could be possible during the squeeze out of ion layers. In fact, recent friction-force measurements with an atomic force microscope conducted in our laboratory 52 show the increase in the activation volume of [C 2 C 1 Im][TFSI] and hence the collective motion of the nanoconfined ions. In these experiments, a silica colloid slides over a mica surface at high compressive stresses.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In the case of studies exploring the potential use of ILs as electrolytes for energy storage devices, adsorbed layers on solid catalysts, or lubricants, signicant efforts have been spent in evaluating the structure and dynamical evolution of solid/IL interfaces as they determine the functional behavior (e.g., charge storage of supercapacitors, friction reduction). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The connement of ILs in nanoscale geometries creates radically different conditions than the ones in the bulk phase, and promotes a strong interaction with the boundaries of the conning matrix, which affects the behavior of ILs (e.g., phase transition, wetting, and ion mobility). 19,21,22 In the case of studies aiming to use ILs as separation or reaction media, the high viscosity and surface tension of these uids compared to conventional organic solvents can lead to unfavorable transport properties.…”
Section: Introductionmentioning
confidence: 99%